Implementasi Nilai-Nilai Pancasila untuk Lawan Bullying, Bahaya Gadget, dan Pentingnya Akta Kematian - Fatmawati, Anisa; Dasmadi, Dasmadi; Ningrum, Rosi Vidya; Mustaghfiroh, Syifa Nurwahidah; Dwira Surya, Bimantaka Ravendra (Society : Jurnal Pengabdian Masyarakat, 2023)
Community service by students is a mentoring and service activity for community development and empowerment in applying technology or social change for the better. The targets for achievement in community service are: (1) increasing public awareness of Pancasila values, (2) preventing acts of bullying, (3) understanding the impact of using gadgets, (4) understanding the importance of death certificates. This activity was carried out in Tempursari Village with the target community and students.